2014
DOI: 10.1111/gtc.12164
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of genomic 5‐hydroxymethylcytosine during mouse oocyte growth

Abstract: Recent studies of the demethylation process in murine zygotes have shown that 5-methylcytosine (5mC) is first converted into 5-hydroxymethylcytosine (5hmC) or further-oxidized cytosines in the paternal genome by the maternal ten-eleven translocation 3 (TET3) enzyme. This process is crucial for normal embryogenesis, and our aim was to elucidate the effect of Tet3 on the maternal genome during female germ-line development. Immunofluorescence analysis showed that 5hmC was clearly present in fully grown oocytes bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
12
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 33 publications
(71 reference statements)
1
12
0
1
Order By: Relevance
“…Analysis of gene expression during oocyte maturation showed no variation in mRNA abundance between GV and MII stages in oocytes derived from adult donors, in accordance with observations during meiotic progression of fully grown oocytes in mouse and pig (Lee et al 2014, Sakashita et al 2014. However, analysis of the transcripts in a model of differential developmental competence revealed an association between TET enzyme expression and oocyte quality.…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…Analysis of gene expression during oocyte maturation showed no variation in mRNA abundance between GV and MII stages in oocytes derived from adult donors, in accordance with observations during meiotic progression of fully grown oocytes in mouse and pig (Lee et al 2014, Sakashita et al 2014. However, analysis of the transcripts in a model of differential developmental competence revealed an association between TET enzyme expression and oocyte quality.…”
Section: Discussionsupporting
confidence: 83%
“…Interestingly, the signal is not uniformly distributed throughout the chromatin, but seems to cluster in restricted areas (dot-like; Fig. 5) as described in growing oocytes in mouse (Yamaguchi et al 2013, Sakashita et al 2014.…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…This expression profile may suggest that during maturation, a DNA demethylation process starts up in the oocyte genome. Sakashita et al () reported the presence of 5hmC in the oocyte genome during maturation. Taken together, these results suggest that TET enzymatic activity (from at least one of the isoforms) exists in oocytes.…”
Section: Discussionmentioning
confidence: 99%